Pemanfaatan Teknologi Openchart sebagai Alat Pendukung Promosi UMKM di Kecamatan X Koto - Ats Tsalis, Fathan; Husein Al Hafidz Alparisi, Muhammad; Elin Puspita, Yulifda (Yayasan Lembaga Studi Makwa, 2023)
This research aims to develop and implement a web-based application, namely Opencart, as a solution to increase the promotion and marketing reach of Micro, Small and Medium Enterprises (MSMEs) in X Koto District. Currently, most of the promotion and marketing of MSME products in X Koto District is still carried out conventionally and only uses general social media so that the reach of promotion is still relatively narrow, limited to only known people. In this era of digital technology, with the development of E-Business and E-Commerce as business media and online buying and selling transactions, MSMEs should be able to follow the flow of global developments in order to increase the reach of product promotion and marketing to a wider range. This research adopts the Research and Development (R&D) model, namely steps to develop new products and improve existing products using the ADDIE (systematic program development) development model. So the aim of this research is to produce a product promotion and marketing media for MSMEs in the form of a web-based application using Opencart application technology. It is hoped that this media can support MSMEs so that they can increase their competitiveness and expand their reach in product promotion and marketing from local, national to international.